At-sea distribution patterns of the Peruvian diving petrel Pelecanoides garnotii during breeding and non-breeding seasons - Claudia E. Fernández; Guillermo Luna-Jorquera; Cristián G. Suazo; Petra Quillfeldt (Scientific Reports, 2023)
Abstract At-sea distributions of seabird species are strongly associated with the distribution patterns of their prey, which are influenced by physical oceanic features. During breeding and non-breeding seasons, seabirds move extraordinary distances among different environments. However, foraging site fidelity by seabirds appears to be high in areas of known high productivity, such as frontal zones and upwellings. Here, we present a tracking study for the Peruvian diving-petrel Pelecanoides garnotii, an endemic seabird of the highly productive Humboldt Current System, to assess whether adults use the same foraging areas throughout the year, combining data from nest monitoring and global location sensors (GLS) deployed on 12 individuals between two breeding seasons (2013–2014 and 2014–2015), in Choros Island (29°15′S; 71°32′W), Chile. Two main foraging areas were registered. During the breeding season, adults moved in the northern direction, between 60 to 144 km away from their colony, foraging in areas with high primary productivity. During the non-breeding period, they moved to southern latitudes (~ 1200 km). Adults spent 37% and 63% of their time in flight/land and on/underwater activities, respectively. We determined that birds move northward from their colony during breeding, where prey availability seems more predictable throughout the year. However, during the non-breeding period, it is likely that other environmental factors influence the distribution pattern of the Peruvian diving-petrel.